أثر توسع الاتحاد الأوروبي على الصادرات الزراعية السورية (Latakia University Journal - Economic and Legal Sciences Series, 2018)
من أبرز التطورات الاقتصادية التي وصل إليها العالم على المستوى الدولي هي ظاهرة التكتلات الاقتصادية بين الدول التي تجمعها مصالح مشتركة سياسية واقتصادية و نتيجة لتلك التطورات الاقتصادية؛ أصبح لا مجال لوجود دولة منفردة تبقى وحدها خارج السرب, وبما أن العمل على توسيع الأسواق هو من الغايات الأساسية لإقامة تلك التكتلات, فلقد كان من الآثار الواضحة لإقامتها أثرها الكبير على التجارة الخارجية لكل دولة من دول التكتل وللدول الأخرى خارج التكتل من خلال علاقتها بالتكتل كوحدة اقتصادية متكاملة.أتت هذه الدراسة لتظهر أثر إحدى تلك التكتلات على صادراتنا الزراعية السورية.حيث يهدف هذا البحث إلى تحليل الصادرات الزراعية السورية إلى الاتحاد الأوروبي منذ فترة نشوئه والتركيز على الفترة من 2000-2010,وذلك من خلال إجراء دراسة تفصيلية للصادرات الزراعية إلى الاتحاد الأوروبي لإظهار أثره على الصادرات الزراعية السورية حيث توصلنا لنتيجة هامة ألا وهي أن للاتحاد الأوروبي أثر على صادراتنا الزراعية وحجم تلك الصادرات إلى دوله.One of the most prominent economic developments reached by the world at the international level is phenomenon of economic blocs between similar countries in the economic, cultural and historical potential and gathered by common interests of the political, economic and as a result of those economic developments; has become no scope for the existence of a single country remains alone outside the flock, and as the work on expanding markets is one of essential objectives for the establishment of such groupings, it has been the obvious effects of their establishment is their impact on the foreign trade of each country of the grouping countries and other countries from outside the grouping through its relationship with the economic grouping as an integrated whole.This study shows the impact of one of those groupings on the Syrian agricultural exports. Where This research aims to analysis Syrian agricultural exports to the European Union since the period of its evolution and focus on the period from 2000-2010, where it shows how the EU grew up till its arrival in current form; and then it shows a detailed study of agricultural exports to the European Union to show its impact on the Syrian agricultural exports where we reached an important result ,that is : the EU has an impact on our agricultural exports and the volume of our exports to its States.